2011
DOI: 10.1080/02619768.2010.516431
|View full text |Cite
|
Sign up to set email alerts
|

The problematic context of mentoring: evidence from an English language teaching department at a Turkish university

Abstract: Mentoring' has become the central issue of the 'restructuring programme' in education faculties in Turkey since 1998. This study aims to explore the participants' perceptions and experiences about the concepts of 'mentor' and 'mentoring'. A mentor and six English Language Teaching Department (ELT) students, who were in the final year of their training programme, participated in the study. A qualitative case study methodology was employed and data were collected through semi-structured interviews with faculty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Anderson, 2007;Russell & Russell, 2011;Sayeski & Paulsen, 2012;Yavuz, 2011). For instance, provision of constructive feedback is considered to be a significant characteristic of the cooperating teachers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson, 2007;Russell & Russell, 2011;Sayeski & Paulsen, 2012;Yavuz, 2011). For instance, provision of constructive feedback is considered to be a significant characteristic of the cooperating teachers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ekiz (2006) also made a contribution in a study conducted with 55 student teachers indicating lack of guidance and assistance from cooperative teachers. The result of the case study conducted by Yavuz (2011) with the six student teachers indicates the guidance provided by cooperating teachers was lacking. Similar to the results of aforementioned studies, the researcher reported that student teachers were mainly concerned about the mentor's failure in giving guidance and providing adequate feedback in the process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were 36 instances of this problem. The main challenges under this category to be For the issues related with receiving feedback from CTs, the studies suggested that the STs considered the feedback provided by CTs problematic, insufficient, and infrequent (Altan & Sağlamel, 2015;Celen, 2016;Mahmoudi & Özkan, 2016;Merç, 2015;Pekkanlı-Egel, 2009;Yavuz, 2011;Rakıcıoğlu-Söylemez & Eröz-Tuğa, 2014;Yördem-Akyol, 2014). The studies underlined the importance of receiving feedback for STs and showed that the feedback given by CTs was deemed to be superficial (focusing on the colors of the materials, not providing detailed feedback on STs teaching performances).…”
Section: Ct Related Challengesmentioning
confidence: 99%
“…Another sub-category of STs' challenges related with practicum identified was the attitudes of CTs towards STs. There were eight studies which reported this problem Çınar, 2010;Merç, 2010;Yavuz, 2011). The literature indicated that the CTs did not regard STs as teachers, displayed discouraging behavior, ignored their questions, were unwelcoming towards STs.…”
Section: Ct Related Challengesmentioning
confidence: 99%